Cyclic phase transformation behavior of nanocrystalline NiTi at microscale. (15th February 2020) - Hua, Peng; Chu, Kangjie; Ren, Fuzeng; Sun, Qingping
Abstract: Cuboidal micropillars of nanocrystalline superelastic NiTi shape memory alloys with an average grain size of 65 nm were fabricated by focused ion beam and then subjected to cyclic compression. It is found that the micropillars have maintained superelasticity for over 10 6 full-transformation cycles under a maximum compressive stress of 1.2 GPa. Functional degradation of the micropillars mainly occurs in the first 10 4 cycles where hysteresis loop area and forward transformation stress rapidly decrease from initial 11 MPa (MJ/m 3 ) and 586 MPa to 6 MPa and 271 MPa. In the 10 4  ~ 10 6 cycles, stress-strain responses of the micropillars show asymptotic stabilization. Residual strain is accumulated to 3.3% and multiple ~50 nm wide extrusions are found at the surface of the micropillars after 10 6 cycles. SEM and TEM studies indicate that cyclic phase transformation results in formation and glide of transformation-induced dislocations that create surface steps and the extrusions. The dislocations inhibit reverse transformation and result in residual martensite and residual stresses. The dislocations and the residual martensite lead to the functional degradation. The role of the residual martensite in the functional degradation is further verified by 21% recovery of the residual strain and an increase of 278 MPa in the forward transformation stress after heating up the cyclically deformed micropillars to 100 °C. The recorded over 10 6 phase transformation cycles under a maximum stress of 1.2 GPa of the NiTi shape memory alloys at microscale open up new avenues for applications of the material in microscale devices and engineering. Graphical abstract: Image, graphical abstract